Cartoons That Time Forgot - From the Van Beuren Studio - VanBeuren, Amadee J.; Gillett, Burt; Palmer, Tom; Stallings, Vernon (image Entertainment, 1998)
Despite its talented staff, the Van Beuren Studio, which existed from 1928 to 1936, never rose above the level of a "B" cartoon house. Their talking version of Felix the Cat, who appears in "Bold King Cole" (1936) and "The Goose That Laid the Golden Egg" (1936), has none of zest of the silent character animated by Otto Messmer. Their original characters, Molly Moo-Cow and Cubby Bear, are awkward-looking nonentities. The "Rainbow Parade" series was clearly designed to compete with Walt Disney's "Silly Symphonies," but the films lack the polished animation, innovative designs, and focused storytelling of the Disney shorts. Some of the Van Beuren cartoons are genuinely odd: "Opening Night" (1933) celebrates the opening of the lavish Roxy Theater in New York; "In a Cartoon Studio" (a.k.a. "Making 'Em Move," 1931) spoofs the animation process with scenes of robust chaos. Modern viewers are more likely to find the rubber-lipped cannibals in "Molly Moo-Cow and Robinson Crusoe" (1936) and the jazz-singing black skeletons in "Wot a Night" (1931) outrageous, if not downright offensive. This is an interesting collection for those interested in animation history, but time - and audiences - has forgotten these cartoons with good reason. [www.amazon.com]
Keywords: DVD-Video